If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-3x) + 8 = 1 + -1(4x) Reorder the terms: 8 + (-3x) = 1 + -1(4x) Remove parenthesis around (4x) 8 + (-3x) = 1 + -1 * 4x Multiply -1 * 4 8 + (-3x) = 1 + -4x Solving 8 + (-3x) = 1 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 8 + (-3x) + 4x = 1 + -4x + 4x Combine like terms: (-3x) + 4x = 1x 8 + 1x = 1 + -4x + 4x Combine like terms: -4x + 4x = 0 8 + 1x = 1 + 0 8 + 1x = 1 Add '-8' to each side of the equation. 8 + -8 + 1x = 1 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 1 + -8 1x = 1 + -8 Combine like terms: 1 + -8 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 24=-6b-2b | | 64*x*2-8=41 | | 12(6-1/2x)=240 | | f(7pi/6) | | h-15=4 | | 6k-7+5k= | | 8(3b+2)=-30 | | http://opt-prod.s3.amazonaws.com/traject/files/item_attachments/relateds/000/429/917/original/Equation_6.PNG?1463559659 | | -6=-7x+8x | | 7.32=0.05-.18 | | f=7*32 | | 25*x*2+2=3 | | .3=0.300 | | 5n^2+1=126 | | 60+70+h=410 | | 3(8-2x)=60 | | 4(1+-12y)-3y=1 | | x*2-7=29 | | 2z(2z+7)-30=0 | | 6S-s= | | 129-43=12 | | 5.75+4.50(k-5)=26.25 | | 4b-11=1-2(3-b) | | 97=28*8+x | | 1.5*0=x-3 | | 14+16=-5(5x-6) | | 97=28+x*8 | | -a-5-(-5)a= | | bx+6=dx-6 | | 10y-7=25y+2 | | 5.92-p=58.63 | | 5-k/7=4 |